Hakekat Keluarga dan Dasar Pembentukan Keluarga - Miftahul Fikri; Neviyarni; Yarmis Syukur (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2021)
Humans are created by living in pairs. The creation of humans from male and female types is the forerunner of human reproduction in order to continue the existence of human life in this world. The purpose of creating a human in a pair, male and female, is so that humans can feel calm and serenity in life, ask each other, and maintain mutual relationships. With the family, it becomes one bridge through which to realize the goal of human creation. This research studies the nature of the family in life. The method in this research is a library research by collecting different references in studying the family. This article summarizes various things about the entire family.